2006
DOI: 10.1677/joe.1.06662
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of hexokinase I in pancreatic islets induced by sucrose administration

Abstract: Administration of a sucrose-rich diet (SRD) to normal hamsters induces an insulin-resistant state and a significant increase of insulin secretion and -cell mass. Islets isolated from these animals had a marked increase in glucose metabolism and glucose-induced insulin secretion, at both low and high glucose concentrations. They also presented increased hexokinase (HK) activity, without measurable changes in glucokinase (GK) activity. In this study we measured HK and GK activity in homogenates of islets isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Conversely, it has been reported that an overload of the β-cell function increases islet hexokinase activity and the HK/GK ratio in rats, rendering the β-cell more sensitive to glucose stimulation at low levels (Leahy, 1996;Hosokawa et al, 1995;Newgard, 1992). This latter effect was also observed in our study, where insulin secretion at 3.3 mM glucose was significantly higher in SRD than in control animals; and the present results resemble those previously published by our group reporting a significant increase in the HK/GK ratio (Massa et al, 2001;Maiztegui et al, 2006). It could thus be assumed that in our SRD-fed hamsters, hexokinase -whose activity is not modulated by insulin -has taken control over the overall glucose metabolism, rendering the islets insensitive to insulin and suggesting that in our model, at least at the timeperiod tested, the β-cell sensitivity to glucose is not decreased as described in human beings with type 2 diabetes or impaired glucose tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, it has been reported that an overload of the β-cell function increases islet hexokinase activity and the HK/GK ratio in rats, rendering the β-cell more sensitive to glucose stimulation at low levels (Leahy, 1996;Hosokawa et al, 1995;Newgard, 1992). This latter effect was also observed in our study, where insulin secretion at 3.3 mM glucose was significantly higher in SRD than in control animals; and the present results resemble those previously published by our group reporting a significant increase in the HK/GK ratio (Massa et al, 2001;Maiztegui et al, 2006). It could thus be assumed that in our SRD-fed hamsters, hexokinase -whose activity is not modulated by insulin -has taken control over the overall glucose metabolism, rendering the islets insensitive to insulin and suggesting that in our model, at least at the timeperiod tested, the β-cell sensitivity to glucose is not decreased as described in human beings with type 2 diabetes or impaired glucose tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…Since PMCA activity decreased in FRD rats by 27%, other mechanisms might contribute to reach the above mentioned increase in [Ca 2+ ] i . The concomitant increase in glucose metabolism measured in islets from rats with FRD-induced IR [44] with the consequent rise in the ATP/ADP ratio and activation of Ca 2+ channels could be one of those mechanisms. These results would suggest that PMCA exerts in vivo a long-term modulation of insulin secretion through changes in cytosolic Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 98%
“…This coordination is subject to a very tight control by many signaling pathways (18): glycolysis and mitochondrial oxidative phosphorylation leading to accelerated ATP generation are two of the most important (16,28). Glycolysis involves high-affinity HKs and low-affinity GCK in most mammalian cells (30). Because the expression levels of high-affinity HKs are very low in islet b-cells, the low-affinity GCK serves as the primary kinase controlling the rate-limiting step of glycolysis in b-cells (4,15,16,39).…”
Section: Discussionmentioning
confidence: 99%